Chronic Trigemino-Cardiac Reflex: An Underestimated Truth - Chowdhury, Tumul; Schaller, Bernhard (Frontiers in Neurology, 2017)
The trigemino-cardiac reflex (TCR) is a brainstem reflex that manifests as adverse cardio-respiratory events upon the stimulation of sensory branches of the fifth cranial nerve. This reflex is mainly investigated in different neurosurgical procedures and intervention. This reflex is commonly considered as an acute and mild physiological response. On the other hand, more devastating and chronic nature of this reflex is largely under-reported and unknown. Therefore, this article aims to provide the comprehensive understanding of the chronic form of TCR, its manifestations, and management by literature search. Also, this paper would certainly impart a better diagnosis and understanding of TCR phenomenon by knowing the relatively less common form of a chronic TCR. This will help thousands and thousands of patients who are still in the phase of diagnosis and are suffering from vague symptoms related to this reflex.